Political Parties and Social Change: Analysis of The Role Political Actors in Modern Society - Eko Wicaksono Nugroho Ndruru (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Abstract In the modern political context, political parties play a crucial role in driving social change and serving as intermediaries between the public and the government. This research aims to explore how political parties confront the challenges of globalization and their role as agents of social change. The methodology employed is a qualitative approach, utilizing secondary data analysis from academic journals, books, and other scholarly sources. The findings reveal that political parties in Indonesia have played a significant role in social transformation, both historically and contemporaneously, such as during the reform era. However, they face internal challenges like leadership issues and corruption, as well as external challenges such as global economic pressures and conservative resistance. Adaptation through policy innovation and building international coalitions are key strategies to address these challenges. This research emphasizes the need for wise management of ideological conflicts to ensure the effectiveness of political parties as agents of change